Imunoexpressão das proteínas efrina-A1 e efrina-B2 e dos receptores EphA1 e EphB4 em lesões periapicais primárias e persistentes - Lima, Wliana Pontes de (2025)
Endodontic treatment of periapical diseases shows a high rate of clinical success, however, in some cases, persistent periapical lesions (LP2) arise, which pose a challenge for Endodontics. In this context, it is essential to deepen the understanding of the pathogenesis of LP2, such as the study of the Eph/ephrin complex, since these proteins act in important biological processes for the development and persistence of LP. Thus, the present study aimed to evaluate, through immunohistochemistry, the expression of ephrin-A1, ephrin-B2 proteins and of the EphA1 and EphB4 receptors in cases of primary periapical lesions (LP1) and persistent. This is a descriptive and analytical laboratory study, in which 20 tissue samples of LP1 (10 periapical granulomas–GP and 10 radicular cysts–CR) and 20 LP2 (10 GP and 10 CR) were investigated. Cases of LP1 and LP2 were included, whose paraffin blocks were in good condition, contained sufficient material, and had properly completed clinical records. Cases without sufficient clinical and radiographic data to differentiate LP1 from LP2 were excluded. In addition, cases of LP2 without a prior history of non-surgical endodontic retreatment, without association with pain, edema, and the presence of a parulis were also excluded. Quantitative analysis of the immunohistochemical expression of ephrin-A1, ephrin B2 proteins and of the EphA1 and EphB4 receptors were performed after analysis of the clinical and morphological parameters and execution of the immunohistochemistry, using the immunoperoxidase method based on the dextran polymer technique. Areas of greatest immunoreactivity for ephrin-A1, ephrin-B2, EphA1, and EphB4 were selected and photomicrographed: five fields in the epithelium and five fields of the fibrous capsule of the CR, as well as five fields of the GP. Then, a count of immunopositive and negative cells was carried out, and the percentage of positivity was established. Subsequently, statistical analysis was performed using the SPSS software (version 25.0; USA), in which it was found that the sample did not show a normal distribution; therefore, non-parametric tests of Mann-Whitney and Kruskal-Wallis were applied, as well as Spearman's correlation test. A significance level of 5% (p<0,05) was considered for all tests. Cytoplasmic immunoexpression of ephrin-A1 was observed in all LP cases. The highest expressions of this protein occurred in CR2, with a statistically significant difference between the cytoplasmic immunoexpression of ephrin-A1 in the epithelium (p=0,002) and connective tissue (p=0,019) of CR2 when compared to CR1. GP1 showed a higher median percentage of positivity than GP2. Among the antibodies evaluated, EphA1 showed the highest medians of cytoplasmic and nuclear immunoexpression percentages, with higher expression in CR2, without statistically significant differences. Ephrin-B2 was expressed in the cytoplasm of all LP, with higher levels of immunoreactivity in the epithelium of CR2 and in the connective tissue of GP1. Nuclear expression of this protein was low in all LP. In turn, the EphB4 receptor showed greater immunoexpression in the epithelium of CR2 and in the connective tissue of CR1 and GP1. There was a statistically significant difference between the cytoplasmic immunoexpression of EphB4 in GP1 (p=0,001) when compared to GP2. Nuclear expression of this receptor was low, except in the epithelium of CR2. No statistically significant correlations were identified between the expressions of the evaluated proteins. Some of the evaluated proteins seem to influence the persistence of LP2, especially in CR2. On the other hand, the EphB4 receptor appears to play a protective role in LP1.